1990
DOI: 10.1021/j100376a022
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of phosphomolybdate adsorption on alumina surfaces. 2. The molybdate/phosphated alumina and phosphomolybdate/alumina systems

Abstract: The adsorption of ammonium heptamolybdate (AHM) on phosphated alumina and of P2Mo50231 23456~a nd PMo^O^3-on 7-Al203 has been studied by using FTIR, Raman, and 31P solid-state NMR spectroscopies, and TPR. Adsorption of phosphate prior to contacting of 7-Al203 with AHM leads to a deactivation of the alumina surface still remaining. Phosphate reacts with 7-Al203 to form an A!P04-type surface phase, which itself is capable of adsorbing molybdate, with the formation of an irreducible surface molybdophosphate, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 1 publication
6
49
0
1
Order By: Relevance
“…4a). The band at 3665 cm −1 is possibly due to ν(P-OH) according to the study of phosphate on γ -Al 2 O 3 where an IR band at 3680 cm −1 was detected and assigned to a P-OH group of supported phosphate [30]. This assignment is supported by the IR spectrum (Fig.…”
Section: Co Adsorption On Mop/siosupporting
confidence: 53%
“…4a). The band at 3665 cm −1 is possibly due to ν(P-OH) according to the study of phosphate on γ -Al 2 O 3 where an IR band at 3680 cm −1 was detected and assigned to a P-OH group of supported phosphate [30]. This assignment is supported by the IR spectrum (Fig.…”
Section: Co Adsorption On Mop/siosupporting
confidence: 53%
“…This is in accordance with literature, in which it is stated that interaction of H x P 2 Mo 5 O 23 (6-x)-with the hydroxyl groups of the Al 2 O 3 supports will result in the disintegration of the complex, when no excess free phosphate is present. 44,46 It is also reported that physisorption of H x P 2 Mo 5 O 23 (6-x)-and Mo 7 O 24 6-can take place on the AlPO 4 layer that has been formed. 46 Impregnation with a Mo-P(1.0) solution results in a reasonably homogeneous distribution of H x P 2 Mo 5 O 23 (6-x)-throughout the support after 90 min.…”
Section: Raman Spectroscopy On the Outer Surface Of Support Bodiesmentioning
confidence: 96%
“…44,46 It is also reported that physisorption of H x P 2 Mo 5 O 23 (6-x)-and Mo 7 O 24 6-can take place on the AlPO 4 layer that has been formed. 46 Impregnation with a Mo-P(1.0) solution results in a reasonably homogeneous distribution of H x P 2 Mo 5 O 23 (6-x)-throughout the support after 90 min. Disintegration of the complex (eq 8) is prevented, as enough free phosphate is present.…”
Section: Raman Spectroscopy On the Outer Surface Of Support Bodiesmentioning
confidence: 96%
See 2 more Smart Citations